1994
DOI: 10.1002/jab.770050411
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of collagenase to particulate titanium: A possible mechanism for collagenase localization in periprosthetic tissue

Abstract: Osteolysis is a central feature of aseptic loosening of orthopaedic joint prostheses. This destructive process is believed to result from phagocytosis of implant wear debris by periprosthetic and synovial macrophages and the subsequent release of proinflammatory mediators, including collagenase. Isolated murine macrophages were cultured in vitro with particulate titanium in order to explore the mechanism of macrophage activation by particulate wear debris. The results, in which the amount of secreted, soluble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…That metal particles could be dangerous to tissues through different mechanisms was suggested by Kane et al (1994), who found titanium particles promoting first collagenase production by macrophages and then strong adsorption of it onto the surface: the enzyme may be responsible for local bone resorption.…”
Section: Metalsmentioning
confidence: 96%
“…That metal particles could be dangerous to tissues through different mechanisms was suggested by Kane et al (1994), who found titanium particles promoting first collagenase production by macrophages and then strong adsorption of it onto the surface: the enzyme may be responsible for local bone resorption.…”
Section: Metalsmentioning
confidence: 96%
“…Titanium readily adsorbs proteins from biological fluids. For instance, some specific proteins including albumin [43,44], laminin V [45], glycosaminoglycans [46], collagenase [47], fibronectin [48], complement proteins [49], and fibrinogen [50] have been found to adsorb onto titanium surface. Titanium surfaces can also support cell growth and differentiation.…”
Section: Biological Propertiesmentioning
confidence: 99%
“…Cyclic mechanical loading, synovial fluid pressure waves, and the natural interface surface formed between the implant and host might favor a combined mechanical and biological dissection along this interface. The binding of collagenases to titanium, 40 and possibly to other biomaterials as well, may further augment this effect. Therefore, the synovial tissue-derived, fluidphase MMPs might contribute to the aseptic loosening of THA.…”
Section: Gelatin Zymographic Analysismentioning
confidence: 99%